Organoleptic Assessment of Cream Soup Formulation "KRIMERA" as a Functional Food Alternative for Anemia Adolescents - Sekarningrum, Abiwardani; Estuti, Wiwit (Jurnal Medisci, 2024)
Anemia is a condition in which the number of red blood cells or the concentration of oxygen carriers in the blood (hemoglobin) in the body is insufficient for physiological needs. Hemoglobin itself functions to help red blood cells to get their natural shape, which is round with a flat center. Anemia is a condition where the body does not have enough iron reserves, so there is a shortage of iron distribution to the body's tissues. Based on the results of Riskesdas in 2018, the prevalence of anemia in Indonesia is still relatively high at 48.9%. This study aims to make functional food alternatives for adolescents with anemia by using raw red bean and brown rice materials to manufacture cream soup and to find out the organoleptic, preferred formulation, nutrient and iron contribution. The method used in this study is an experimental method with a RAL (Complete Random Series) research design with two repetitions and as many as eight experimental units with four formulas with comparisons in the use of red beans and brown rice F0 (0%: 13%), F1 (10.4%: 2.6%), F2 (9.1%: 3.9%), and F3 (7.8%: 5.2%). The results of the most preferred red bean and brown rice cream soup formulation product based on the overall parameter with the highest value is the first formulation (F1) with a value of 4.10. This value is higher than the F0 value of 3.87, so this product can be used as an alternative functional food for anemia sufferers.